2018
DOI: 10.18203/2394-6040.ijcmph20183087
|View full text |Cite
|
Sign up to set email alerts
|

Interns willingness to serve in rural area: a cross sectional survey in a government medical college, Mysore

Abstract: Background: India's health workforce has a diversity of health workers offering health services in several systems of medicine. There is uneven distribution and this scarcity is due to both the disinclination of qualified private physicians to work in underserved areas and the inability of the public sector to adequately staff rural health facilities. The objective of the study was to assess willingness of interns to comply with their commitment of serving in a rural area after internship completion and to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…Samanta S et al Int J Community Med Public Health. 2023 Sep;10(9):3196-3201 International Journal of Community Medicine and Public Health | September 2023 | Vol 10 | Issue 9 Page 3200half of the interns were ready to serve through the compulsory rural posting bond if they get benefit for a post-graduation seat, higher pay, whereas the present study observed 33% participants to have similar views 6. …”
contrasting
confidence: 51%
See 1 more Smart Citation
“…Samanta S et al Int J Community Med Public Health. 2023 Sep;10(9):3196-3201 International Journal of Community Medicine and Public Health | September 2023 | Vol 10 | Issue 9 Page 3200half of the interns were ready to serve through the compulsory rural posting bond if they get benefit for a post-graduation seat, higher pay, whereas the present study observed 33% participants to have similar views 6. …”
contrasting
confidence: 51%
“…The present study showed about 78% students were not willing to serve the rural areas during the internship which is higher than the studies conducted by Jayashree et al in Mysore (58%) and Gaikwad et al in Bangalore (66%), where as it was in accordance with the studies conducted on doctors of Goa. [6][7][8] Though our study revealed that about 65% students opined that it would be beneficial to the rural population, but they are not in favour of mandatory rural service as a part of MBBS which was similar with the findings of Boviskar et al in Mumbai (80%) but was in contrast with the study conducted by Wiwanitkit in Thailand where rural health service system largely solved the problem of an inadequate number of physicians and other health-care workers in rural areas. 9,10 Many other Indian states such as Karnataka, Odisha, Kerala, Maharashtra, Goa, and Chhattisgarh tried to introduce the compulsory rural service but failed as most of the students were willing to pay fine instead of joining compulsory rural services, the picture was not very different in West Bengal, where 46% thought bond money is a good wayout.…”
Section: Discussionmentioning
confidence: 99%